Psychosocial Stressors and Construction Labor Productivity: A Review - Nishadini, P.L.K.A.; Bhagyani, A.A.B. (NSBM Green University, 2022)
Stress caused when exposed to various psychosocial risks/hazards at work is simply known to be psychosocial stressors. Worker productivity is considered as a crucial element within any organization as it measures the rate at which work is performed. It is generally a known fact that regardless of the cause, any worker experiencing stress in the workplace will showcase a decreased productivity. The paper presents a review of psychosocial stressors and its impact on construction labor productivity from the year 2005 to 2022. Applying content analysis with systematically selected six journal articles, it reviews empirical studies on how the psychosocial stressors have an impact on the construction labor productivity. The objective of research is to understand what psychosocial risks exist within a workplace and how it impacts on the labor productivity of the workers.This review explored on the mediating role of health, specifically mental and social disorders between psychosocial stressors and labor productivity in accordance with the empirical link. This paper will contribute to the literature on labor productivity, since there is a scarcity of literature related to the impact of the psychosocial stressors on Labor productivity.